P420 Safety & feasibility of targeted mesenteric approaches to ileocolic resection and anastomosis in Crohn's Disease. (30th January 2023) - Holubar, S; Cohen, B; Uchino, T; Lincango, E; Prien, C; Joseph, A; Achkar, J P; Gunter, R; Lashner, B; DeLaney, C; Ban, K; Bolshinsky, V; et al.
Abstract: Background: More than 80% of patients with Crohn's disease (CD) require surgical intervention during their lifetime. High rates of disease recurrence often necessitate repeat surgery. Recurrence is typically observed at or immediately proximal to the anastomosis, raising the question of whether surgical techniques have the potential to decrease recurrence rates. In addition, the mesentery has recently been implicated in the pathophysiology of CD, and several techniques have been developed to reduce its influence on recurrence. We aimed to describe the short-term safety and feasibility of these approaches. Methods: This is a comparative retrospective single-center cohort study of consecutive CD patients undergoing primary or redo ileocolic resection with mesenteric excision and exclusion (MEE), extended mesenteric excision (EME) only, or Kono-S anastomosis (KSA) only from 2015-2022. Patients undergoing both EME plus KSA were considered to have MEE. Patients' characteristics, perioperative data, and short-to-midterm outcomes were collected. Univariate analysis was performed. Results: A total of 186 patients underwent MEE (n=46), EME (n=66), or KSA (n=74). All three groups had comparable (p>0.05) risk factors in terms of mean age at diagnosis and surgery (25.4 and 37.5 years old, respectively), preoperative biologics (63.4%) and corticosteroids (22.6%), smoking, and associated perianal disease. However, the MEE group had more penetrating disease compared to the other groups (MEE 50.0% vs. EME 34.8% vs. KSA 20.4%; p<0.01). Overall there were no differences (p>0.05) in rates of emergency surgery (4.8%), ileostomy creation (14%), and laparoscopy (64.5%) Table 1. Estimated blood loss and length of stay were also comparable between groups (p>0.05). Operative time in the MEE group was longer (median: 187, range: 67-360 minutes) compared to the other two groups (KSA: 170 (56-487); EME: 152 (63-436, p<0.01). Post-operatively, the groups had similar lengths of stay (4 days), rates of readmissions (9.1%) and major postoperative complications (6.5%). After a median overall follow-up of 8 months (0-86), endoscopic (18.8%) and surgical recurrences (1.1%) did not differ between groups (p>0.05) Table 2. Conclusion: Targeting the mesentery with novel surgical approaches to ileocolic Crohn's disease was observed to be safe and feasible on short-term follow-up. Long-term follow-up is needed to assess the impact of these techniques on post-operative anastomotic disease recurrence.